Muju Virus, Harbored by Myodes regulus in Korea, Might Represent a Genetic Variant of Puumala Virus, the Prototype Arvicolid Rodent-Borne Hantavirus - Lee, Jin Goo (MDPI, 2014)
The genome of Muju virus (MUJV), identified originally in the royal vole (Myodes regulus) in Korea, was fully sequenced to ascertain its genetic and phylogenetic relationship with Puumala virus (PUUV), harbored by the bank vole (My. glareolus), and a PUUV-like virus, named Hokkaido virus (HOKV), in the grey red-backed vole (My. rufocanus) in Japan. Whole genome sequence analysis of the 6544-nucleotide large (L), 3652-nucleotide medium (M) and 1831-nucleotide small (S) segments of MUJV, as well as the amino acid sequences of their gene products, indicated that MUJV strains from different capture sites might represent genetic variants of PUUV, the prototype arvicolid rodent-borne hantavirus in Europe. Distinct geographic-specific clustering of MUJV was found in different provinces in Korea, and phylogenetic analyses revealed that MUJV and HOKV share a common ancestry with PUUV. A better understanding of the taxonomic classification and pathogenic potential of MUJV must await its isolation in cell culture.